2013
DOI: 10.1136/sextrans-2013-051184.0286
|View full text |Cite
|
Sign up to set email alerts
|

P2.021 Prevalence of Sexually Transmitted Infections in Young People in St. Petersburg, Russia, as Determined Using Self-Collected Non-Invasive Specimens

Abstract: The prevalence of syphilis with RP and TPHA was 0.9% (12/1400). RTs for syphilis showed > 90% sensitivity and 100% specificity. RTs for C trachomatis showed a low sensitivity between 22 -37% and a 99% specificity, RTs for N gonorrhoeae showed 97%. Conclusions In women with symptoms of LGTIs RTs used at the point of care for syphilis have a sensitivity > 90%. RTs for CT have sensitivity < 40% and Rts for NG have sensitivity < 12.5% %.Funded Background Young people are worldwide a risk group for sexually transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We included 11 studies, 6 of which were in countries with higher HDI (Denmark 1, 24 Great Britain 2 and Great Britain 4, 25 26 Norway 4, 27 Russian Federation 3 28 and USA 2, 20 n=13 331) and five in countries with a lower (Honduras 1, 21 Vietnam 1, 22 Kenya 1, 29 Madagascar 1, 30 Tanzania 1, 23 n=4978) HDI ( figure 1 , online supplementary table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…We included 11 studies, 6 of which were in countries with higher HDI (Denmark 1, 24 Great Britain 2 and Great Britain 4, 25 26 Norway 4, 27 Russian Federation 3 28 and USA 2, 20 n=13 331) and five in countries with a lower (Honduras 1, 21 Vietnam 1, 22 Kenya 1, 29 Madagascar 1, 30 Tanzania 1, 23 n=4978) HDI ( figure 1 , online supplementary table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eighty per cent of studies (36 of 45) detected newly diagnosed positive CT/GC infections and 42.2% of studies (19 of 45) measured test accuracy 16 17 20 22–55. Seventeen studies reported 2×2 table values 22 28 30–33 35 36 38–43 51–53.…”
Section: Resultsmentioning
confidence: 99%